Start time: 6:30 PM
start time: 2 hours 18 min
end time:________

Answers

Answer 1
Answer: Start time: 6:30 PM
start time: 2 hours 18 min 
end time: 8:48 PM
Answer 2
Answer: If you started at 6:30, 2 hours and 18 minutes later would be 8:48. 
The end time would be 8:48 p.m. 

Related Questions

Help me please I'm having trouble with this problem ​
Please help with #1 on geometry section
Some one help me please
Ben drinks tea at an incredible rate. He drinks 3\dfrac123 21​ liters of tea every \dfrac23 32​ of an hour. Ben drinks tea at a constant rate.How many liters of tea does he drink in one hour?
A pet store had 149 goldfish and 914 angelfish. Within a week, the difference between the amount of each fish had 3 tripled. Write an expression that shows the current difference between the number of each type of fish.

A shopper bought shoes marked $40. the sales tax is 8%. how much did the shopper pay in all

Answers

8% equals 3.2. If you add $40 plus $3.2 cents that shopper would of paid $43.2 cents.

Answer:

43.2

Step-by-step explanation:

You only have to:

1-convert 8% to a decimal moving the point twice to the left.

2-multiplying 40 by 0.08

3- add the product of the multiplication that you just did and that will give you the answer✨

Amber is using 3 ft by14 ft sheets or wallpaper to cover a rectangular wall that has an area of 240ft^2. What is the least number of sheets of wallpaper she will need?

Answers

3ft x 14ft = 42ft^2


 240ft^2
----------
 42ft^2

5.7

So she needs 6 sheets. 

What is the solution to the equation 8-2b= -2/3(12b+6) ?

b =??????????????

Answers

ok so remember you can do anything to an equaiton as long as you do it to both sides

-8-2b=-2/3(12b+6)
distribute so we can work with innter terms
a(b+c)=ab+ac
-2/3(12b+6)=-24b/3-12/3=-8b-4

we now have
8-2b=-8b-4
get all b's on one side
add 8b to both sides
8+8b-2b=8b-8b-4
8+6b=0-4
8+6b=-4
subtract 8 fro both sides
8-8+6b=-4-8
0+6b=-12
6b=-12
divide both sides by 6
6/6b=-12/6
1b=-2
b=-2



b=-2

So the answer would be b=-2. The steps of this is you would refine -2/3 (12b+6) to -4(2b+1) so then the equation would turn into 8-2b= -4 (2b+1). Then you would expand -4(2b+1) into -8b+4. So now the equation is 8-2b=-8b-4. Then you'd subtract 8 from both sides: 8-2b-8=-8b-4-8 which is -2b=-8b-12. Then you'd add 8b to each side. -2b+8b=-8b-12+8b that equals 6b=-12. Then you divide both sides by 6: 6b/6=-12/6. Then you get b= -2. Hope this helped. 

Determine the quotient of 3/5 and 2/3

Answers

The quotient of 3/5 and 2/3 is 9/10 and this can be determined by using the arithmetic operations.

Given :

Number 1 - 3/5

Number 2 - 2/3

The following steps can be used to determined the quotient of 3/5 and 2/3:

Step 1 - First, divide 3/5 by 2/3.

=((3)/(5))/((2)/(3))

Step 2 - Now, multiply 3/5 and 3/2.

=(3)/(5)* (3)/(2)

Step 3 - Multiply 3 and 3 in the above expression.

=(9)/(5* 2)

Step 4 - Multiply 5 and 2 in the above expression.

=(9)/(10)

The quotient of 3/5 and 2/3 is 9/10 and this can be determined by using the arithmetic operations.

For more information, refer to the link given below:

brainly.com/question/3075170

Answer:

The result is (9)/(10)

Step-by-step explanation:

Below are the steps to divide fractions:

  1. The 1st fraction remains untouched.
  2. The division sign turns into a multiplication sign.
  3. Flip the 2nd fraction over (finding its reciprocal)
  4. Multiply the numerators (top numbers) together
  5. Multiply the denominators (bottom numbers) together.
  6. Simplify the resulting fraction by dividing both numerator and denominator by the same number.

Let's follow the above steps:

Steps 1, 2 and 3 can be done together.

(3)/(5):(2)/(3) = (3)/(5).(3)/(2)

As you can see, we leave 1st fraction alone, change division sign (:) by multiplication sign (.), and flip 2nd fraction over.

Now, we can do steps 4 and 5...

(3)/(5):(2)/(3) = (3)/(5).(3)/(2) = (3.3)/(5.2) = (9)/(10)

Finally, step 6, we cannot simplify the resulting fraction since both numerator and denominator have no common factors.

9 = 3 . 3

10 = 2 . 5

T is to 9 as 7 is to 39

Answers

Answer:

T = 21/13

Step-by-step explanation:

Step 1:  Make an expression

T is to 9 as 7 is to 39

(T)/(9) = (7)/(39)

Step 2:  Cross multiply

(T)/(9) = (7)/(39)

39(T) = 7(9)

39t = 63

Step 3:  Divide both sides by 39

39T / 39 = 63 / 39

T = 21 / 13

Answer:  T = 21/13

Which equation best represents this situation? The number 46 is equal to 23 multiplied by an unknown number.



A.


46 = 23 ÷ p


B.


46 = 23p


C.


46 = 23 – p


D.


46 = 23 + p
NEED help plz!

Answers

So since the problem says the number 46 is equal to something, you immediately know that your equation will look like this

46 = something

Now, when an unknown number is multiplied by a number, it has the number and a letter right next to it.

example.  23p

So since 23p = 46, your answer is B :) Hope this helped!
it's B because p is used as the unknown number here and some ways of saying multiplication is
23 x p
23 (dot in the middle) p
or 23p
since the qw says the number 46 is equal to it is
46=
so the answer is B) 46=23p